Diversity of Northwest Pacific atmospheric circulation anomalies during post-ENSO summer - Tao, Weichen; Kong, Xiangwei; Liu, Yong; Wang, Ya; Dong, Danhong (Frontiers in Environmental Science, 2022)
In present study, the diversity of summertime Northwest Pacific (NWP) atmospheric circulation anomalies following El Niño-Southern Oscillation is investigated by performing the inter-case empirical orthogonal function (EOF) analysis among 33 El Niño cases and 36 La Niña cases, respectively. Although an anomalous anticyclone is observed over the NWP for all El Niño cases’ composite, the circulation anomalies there vary from one case to another for each case. The EOF1 mode of NWP circulation anomalies explains 39.8% of inter-case variance, and its positive phase features an anomalous anticyclone and cyclone at south and north of 25°N, respectively. Therefore, the positive first principal component (PC1) corresponds to the anomalous NWP anticyclone, while the anticyclone shifts more northeastward and a cyclone appears at its south side for negative PC1. The PC1-related NWP circulation anomalies are largely controlled by the pronounced central and eastern Pacific sea surface temperature cooling, which indicates the diverse El Niño decay rate. Furthermore, four categories are obtained according to the El Niño decay rate by the nonlinear k-means cluster analysis, and the results further confirm that the close relationship between NWP circulation anomalies and El Niño decay rate. The PC1-regressed land rainfall anomalies highly resembles the composite results in the key areas of Asian monsoon region: the central China and South Asia, indicating variable rainfall anomalies in these areas during post-El Niño summer. The conclusions obtained from La Niña cases are generally same to El Niño.